2022
DOI: 10.3390/ijerph19116802
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes in the News: Readability Analysis of Malaysian Diabetes Corpus

Abstract: This paper describes a study to evaluate the readability scores of Malaysian newspaper articles meant to create awareness of diabetes among the public. In contrast to patient-specific sources of information, mass media may potentially reach healthy people, thus preventing them from becoming part of the diabetes statistics. Articles published within a selected corpus from the years 2013 to 2018 and related to awareness regarding diabetes were sampled, and their readability was scored using Flesch Kinkaid Readin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“… 29 However, a recent study from Malaysia reported that there was much room for improvement in the language such as using simple sentence structures in newspapers. 30 All media including newspapers have a very good role in improving diabetes health literacy. Other than newspaper reading, internet use, and glucose monitoring, we did not capture information on other diabetes self-care practices which are reported to be effective in improving diabetes control rates.…”
Section: Discussionmentioning
confidence: 99%
“… 29 However, a recent study from Malaysia reported that there was much room for improvement in the language such as using simple sentence structures in newspapers. 30 All media including newspapers have a very good role in improving diabetes health literacy. Other than newspaper reading, internet use, and glucose monitoring, we did not capture information on other diabetes self-care practices which are reported to be effective in improving diabetes control rates.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes is emerging as an epidemic all over the world, and it is a common chronic disease that seriously threatens human health [ 2 ]. It affects the quality of lives of many people around the world [ 3 ], and the quality of life for Chinese residents is also affected by diabetes. China has a large and rapidly growing elderly population.…”
Section: Introductionmentioning
confidence: 99%